Sustainable intensification of livestock as a means to achieve forest conservation and food production in the Brazilian Southern Atlantic forest. Issue 6 (3rd July 2021) - Castelo Branco Brasileiro-Assing, Andréa; Wironen, Michael; Adams, Alison; Farley, Joshua; De Almeida Sinisgalli, Paulo Antonio; Schmitt-Filho, Abdon
ABSTRACT: Brazil's Atlantic Forest is a biodiversity hotspot. Efforts to restore the forest must address the tradeoffs facing family farmers. In this paper, we combine literature review and empirical analysis to evaluate the ways in which an agroecological practice – Management Intensive Grazing (MIG) – can contribute to sustainable intensification in southern Brazil. Our results show that farmers adopting MIG obtained, in general, better economic and environmental performance, but did not completely renounce the use of external inputs. Forest cover appears to have increased since the promotion of MIG and agroecology in the region and pasture area decreased, therefore, benefiting forest conservation.